Chiral phthalimides against penicillin-binding protein 2a of methicillin-resistant Staphylococcus aureus: molecular docking and in vitro analysis - Khan, Aamina Azam; Khan, Momin; Khan, Sher Wali; Siddique, Nayyer; Abid, Rimsha; Zulfiqar, Shandana; Rahman, Sidra; Ali, Muhammad (Frontiers in Pharmacology, 2024)
Staphylococcus aureus (S. aureus) is a commensal bacterium and an opportunistic pathogen causing a wide variety of infections ranging from localized skin and soft tissue infections to life-threatening severe bacteremia, osteomyelitis, endocarditis, atopic dermatitis, prosthetic joint infections, staphylococcal food poisoning, medical devices related infections and pneumonia. It is attributed to an acquired resistant gene, mecA, encoding Penicillin-binding Protein 2a (PBP2a). PBP2a is an essential protein responsible for the resistivity of Methicillin-resistant Staphylococcus aureus (MRSA) to various beta-lactam antibiotics. The antimicrobial treatment alternatives for MRSA are increasingly limited. Therefore, developing alternative therapeutic options for its treatment is the need of the day. Phthalimides and their N-substituted derivatives are of biological importance as they possess extensive biological and pharmaceutical properties and can serve as an excellent therapeutic option for MRSA. This study uses three chiral phthalimides (FIA, FIB, and FIC) to check their in silico and in vitro inhibitory effects. Molecular docking of these chiral phthalimides against PBP2a of MRSA was performed initially. After promising results, these novel compounds were screened through the agar well diffusion method and micro-broth dilution assay to investigate their in vitro inhibitory activity with FIB being the strongest anti-staphylococcal agent yielding a 21mm zone of inhibition and MIC of 0.022ug respectively. The zones of inhibition obtained through the in vitro activity showed that these chiral phthalimides possess substantial anti-MRSA activities and have the potential to be considered as alternative chemotherapeutics to treat the infections caused by MRSA after the confirmation of their cytotoxic and pharmacokinetic studies.